"ABDULLA QAHHOR'S SKILL OF USING INDIVIDUAL ARTICLES (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
This article highlights the importance of using word-rich articles, as well as methods of utilizing them, illustrated through the works of Abdulla Qahhor.